2021
DOI: 10.1111/clr.13795
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effectiveness of 6 mm micro‐rough implants in various indications: A 4.6‐ to 18.2‐year retrospective study

Abstract: Objectives To evaluate the long‐term effectiveness of 6 mm implants in various indications with a micro‐rough surface after 4.6–18.2 years in function and to assess key factors associated with implant survival, success, and biologic/technical complications. Materials and methods Fifty‐five patients with seventy‐four 6 mm implants placed from 2000 to 2013 attended the re‐examination assessing well‐established clinical and radiographic parameters, biologic and prosthetic complications, and patient‐reported outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Rough surfaces are also believed to yield better osseointegration than smooth surfaces. This, subsequently, may enable more osteoblast cells to adhere and proliferate on the surface of Zr implants [42,43]. However, it is difficult to achieve sufficient surface roughness in Zr implants using methods that are typically used for Ti implants [44].…”
Section: Discussionmentioning
confidence: 99%
“…Rough surfaces are also believed to yield better osseointegration than smooth surfaces. This, subsequently, may enable more osteoblast cells to adhere and proliferate on the surface of Zr implants [42,43]. However, it is difficult to achieve sufficient surface roughness in Zr implants using methods that are typically used for Ti implants [44].…”
Section: Discussionmentioning
confidence: 99%
“…Dental implants are the primary and most predictable treatment approach to replacing missing teeth 1,2 . Despite their high success rate and longevity 2,3 around 20%–25% of dental implants are affected by peri‐implantitis after 5–10 years of implant placement 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Dental implants are the primary and most predictable treatment approach to replacing missing teeth 1,2 . Despite their high success rate and longevity 2,3 around 20%–25% of dental implants are affected by peri‐implantitis after 5–10 years of implant placement 4,5 . Similarly to periodontitis, peri‐implantitis is defined as a biofilm‐associated pathologic condition affecting the tissue around dental implants, characterized by inflammation in the peri‐implant mucosa and subsequent progressive loss of supporting bone 6,7 …”
Section: Introductionmentioning
confidence: 99%
“…Patients may not show the same self-perception and psychosocial impacts because of different demographics, such as age, gender, educational status, tooth loss number, smoking habit, simultaneously bone augmentation, loading timing and prosthesis type [ 14 , 15 ]. Previous studies have showed higher occurrence of tooth loss by periodontitis and subsequent implant failure in patients with smoking habit, which may cause a contradictory psychological need for the balance of the anterior implant treatment and the addiction to smoking [ 16 , 17 ]. Anterior implants involve the comprehensive solutions of surgery and prosthetics, such as simultaneously bone augmentation, loading timing and prosthesis type [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%